Effectiveness of Goat Urine Liquid Organic Fertilizer with Different Empon-Empon Starters on The Quantitative Production of Odot Grass - Windyasmara, Ludfia; Nur Rohman, Azis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This research explores the utilization of goat urine as the main ingredient in the production of Liquid Organic Fertilizer (LOF), enhanced with herbal additives (empon-empon) as natural fermentation starters. The study aims to provide an environmentally friendly and sustainable alternative to chemical fertilizers by transforming goat farming waste into productive agricultural input. Two herbal starter formulations were developed using ingredients such as ginger, turmeric, papaya leaves, sprout extract, and coconut water. These formulations were applied to Odot grass (Pennisetum purpureum cv. Mott) as the test crop over a 30-day period. Growth parameters including plant height, number of leaves, fresh weight, and dry weight were measured and statistically analyzed using Independent Sample T-Test. The results showed no significant differences between the two treatments across all measured variables, although starter A showed a slightly higher average performance in fresh and dry biomass production. The findings suggest that both formulations of LOF are viable and contribute to sustainable agricultural practices by improving soil fertility and promoting healthy plant growth through natural inputs.